Reconstruction of past heavy metal concentration in the sediment using the seagrass Enhalus Acoroides (L.F.) royle as a biological indicator - Quebral, Ricardo Diaz (2001)
Bioindicators of heavy metals often describe the recent changes in concentration levels in the marine environment rather than the past metal concentration profile. A correlational study was conducted to test the possibility of reconstructing the historical profile of heavy metal concentration in the sediment by analyzing metals absorbed by the seagrass Enhalus acoroides. Copper, cadmium, lead, and zinc which accumulated in annual sections of the rhizomes and dead leaf fibers of the seagrass were correlated with the concentration levels in the sediment for the corresponding years.